Konsep Pendidikan Ibadah Berdasarkan Al-Qur'an dan Hadits - Lina Zakiah; Ahmad Saefurridjal; Iskandar Mirza (PT. Pusmedia Group Indonesia, 2024)
The Qur'an is the revelation of Allah Swt which was revealed to the Prophet Muhammad Saw as a guide for the entire life of mankind, not only Muslims in particular. For this reason, the Qur'an is an oasis in human life which is used as a guide in life. The originality of the Qur'an as a holy book is guaranteed unlike other books, which until now have no authentic and original, as a result of human behavior that dares to change and distort and there is no guarantee of certainty of originality.Whereas in the Qur'an and Prophetic Hadiths discussing the issue of immortality or servitude to God is one of the responsibilities of humans and Jinn by nature created by God. So that all the dynamics of human life on earth should be based on the principles and values of ubudiyah, both activities that are political, educational, economic, social, and so forth. According to Imam al Thabari in his tafsir; that the purpose of Allah creating humans and jinn is to serve Him, if they do good then they will be rewarded with rewards, but if they do bad, then they will be rewarded with punishment later on the Day of Judgment. This is not based on Allah's need for humans to worship Him, but for the sake of benefit and the benefits also return to humans themselves. Keywords: Worship Education; Al-Qur’an; Hadith